Mental health and behavioural factors involved in road traffic crashes by young adults: analysis of the Raine Study. Issue 6 (27th December 2021) - Tait, Robert; Ivers, Rebecca; Marino, Jennifer L; Doherty, Dorota; Graham, Petra L; Cunich, Michelle; Sanci, Lena; Steinbeck, Katharine; Straker, Leon; Skinner, S Rachel
Abstract : Background: Road traffic crashes (RTC) are a leading cause of mortality and morbidity in young people. Severe mental health and behavioural conditions increase the likelihood of RTC, as do a range of driving-risk activities. Method: We used data from the Raine Study, a prebirth cohort from Perth, Australia, to assess the relationship between measures of common mental health or behavioural conditions (Child Behavior Checklist Internalising and Externalising scores) at age 17 and subsequent RTC by 27 years, controlling for substance use and driving-risk activities. Results: By 27 years of age, of 937 participants, 386 (41.2%) reported zero crashes and 551 (58.8%) reported ≥1 crashes. In the baseline Poisson model, increased Externalising scores (eg, aggression and delinquency) were associated with increased RTC (incidence rate ratio (IRR)=1.02, 95% CI 1.01 to 1.02): increased Internalising scores (eg, anxiety and depression) were associated with fewer RTC (IRR=0.99, 95% CI 0.98 to 1.00). In the fully adjusted model, the mental health measures were not significant (Externalising IRR=1.01, 95% CI 0.99 to 1.02: Internalising IRR=0.99, 95% CI 0.99 to 1.00). Risky driver activities, such as falling asleep while driving (IRR=1.34), more frequent use of a hands-free telephone (IRR=1.35) and more frequent hostility towards other drivers (IRR=1.30) increased the rate of RTC. Conclusion: Measures of mental health scores at age 17 were not predictive of subsequent RTC, after adjusting for measures of driving-risk activities. We need to better understand the determinants of externalising and risky driving behaviours if we are to address the increased risk of RTC.